Improvement of grain processing via ultrasonic treatment - Rudik, F. Ya.; Morgunova, N. L.; Semilet, N. A.; Tuliyeva, M. S. (IOP Conference Series: Earth and Environmental Science, Conference on Innovations in Agricultural and Rural development (18–19 April 2019)., 2019)
The theoretical study made it possible to define the main correlation dependences affecting the efficiency of grain preparation for milling. Experimental studies allowed improving the technology of grain softening and washing. Design and operating parameters of ultrasonic facility and technology ensuring high degree of grain cleaning and moistening were studied and structured, namely: ultrasound frequency – 18 kHz; process temperature – 30-40 °C; processing time – 30-40 s; intensity of ultrasonic waves – 1 W/cm2.Теоретическое исследование позволило определить основные корреляционные зависимости влияет на эффективность подготовки зерна к помолу. Экспериментальные исследования позволили улучшить технология размягчения и промывки зерна. Конструкция и рабочие параметры ьтразвукового Изучено устройство и технология, обеспечивающие высокую степень очистки и увлажнения зерна. структурированные, а именно: частота ультразвука – 18 кГц; температура процесса – 30-40 °С; обработка время – 30-40 с; интенсивность ультразвуковых волн – 1 Вт/см2.
Keywords: импакт-фактор 2019; скопус; конференции; зарубежные авторы; обработка зерна; помол зерна